An Analytical Study on Lecturer Development Management at the College of Islamic and Arabic Studies (STIBA) Makassar - Ridwan, Muhammad; Muh. Wayong; Musdalifah, Musdalifah; Fauziah Ramdani (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
This article examines the management of faculty development at STIBA Makassar as a strategic foundation for strengthening the Tridarma of higher education. The study aims to analyze specific dimensions of faculty development—pedagogical competence, research productivity, and career advancement—while assessing management aspects such as budgetary allocation, supervisory consistency, and institutional incentive systems. A qualitative case study approach was employed, involving ten informants selected through purposive sampling, including institutional leaders, department heads, and senior lecturers. Data analysis followed a thematic approach with an inductive-deductive coding process, ensuring trustworthiness through source triangulation. The findings reveal that while STIBA Makassar demonstrates strong institutional commitment, implementation faces structural hurdles, including budget constraints and excessive teaching workloads that stifle research productivity. However, the P3M unit has shown progress through AI-based writing and OJS digitalization. By synthesizing these findings with Human Resource Development and Motivation theories, this research contributes a Hybrid Management Model that integrates modern professional accountability with traditional Islamic institutional values. These results provide a strategic roadmap for building a sustainable, quality-oriented faculty development system in pesantren-based institutions.